Expression patterns and clinical significance of MMP-8, MMP-9 and MMP-13 in colorectal cancer: mmp-8, mmp-9 and mmp-13 expression in colorectal cancer - Ghadyani, Rezvaneh; Mozooni, Zahra; Sohbatzadeh, Zihab; Gachkar, Latif; Sepehr Kahrizi; Movafagh, Abolfazl (Cellular and Molecular Biology, 2025)
Colorectal cancer (CRC) is the most common malignancy of the gastrointestinal system in the world. By identifying specific gene expression patterns that indicate CRC in the early stages, it is possible to potentially diagnose the disease in the early stages and start treatment quickly. Matrix metalloproteinases (MMPs) play a crucial role in the degradation of the extracellular matrix and tissue remodeling. Among them, MMP-8, MMP-9 and MMP-13 have been found to be upregulated in various cancers, including CRC, and are associated with tumor invasion, metastasis, and angiogenesis. This study investigated tissue expressions of MMP-8, MMP-9, and MMP-13 in CRC patients and explored their possible associations with pathological and clinical factors. 100 patients with CRC and 100 control subjects were involved in the study. Tissue and blood samples were collected. The quantitative Real-Time PCR (qRT-PCR) technique was used to assess the expression levels of the MMP-8, MMP-9, and MMP-13 in CRC tissue samples in comparison with the adjacent control tissue. Our results revealed that the expression levels of MMP-8, MMP-9, and MMP-13 were significantly up-regulated in CRC tissues compared to the adjacent control group. Analysis of patients’ clinicopathological features showed a statistically significant difference in the expression levels of MMP-8, MMP-9, and MMP-13 between CRC patients with and without lymphovascular invasion (LVI) and TMN stage. ROC curve results have shown that these genes are good candidate diagnostic biomarkers in CRC. These results indicated that MMP-8, MMP-9, and MMP-13 levels may serve as potential diagnostic biomarkers for CRC.